An annotated checklist of ladybeetle species (Coleoptera, Coccinellidae) of Ferghana Valley (Uzbekistan) - Saodat T. Gafurova; Bakhtiyor R. Kholmatov; Gulnara S. Mirzaeva (Acta Biologica Sibirica, 2025)
The article presents the results of a study on the fauna of lady beetles (Coleoptera, Coccinellidae) based on our observations in the Fergana Valley during the spring, summer, and autumn seasons as well as the winter season from 2022 to 2024. Thirty-five species of lady beetles, belonging to 5 subfamilies (Scymninae, Chilocorinae, Ortaliinae, Coccinellinae, and Hyperaspidinae), 9 tribes, and 19 genera, were found along the valley. Noteworthy species identified in the Fergana Valley during the research include Novius yemenensis (Raimundo & Fürsch, 2006), Platynaspidius saundersi (Crotch, 1874), Brachiacontha ursine (Chevrolat in Dejean, 1837), Scymnus marinus (Mulsant, 1850). The species Calvia muiri (Timberlake, 1943) and Clitostethus arcuatus (Rossi, 1794) were recorded for the first time in the fauna of Uzbekistan and 23 species were recorded for the first time in the Fergana Valley.